(untitled) (Nordic Journal of African Studies, 2020)
Departing from two qubba-s, beehive-like tombs from the 19th century in the centre of Khartoum, the author portrays the complicated sequence of power politics in Egypt and in the Sudan, which ’explains’ the existence of those two burial monuments in an area where most such monuments were destroyed after the Mahdi’s conquest in 1885. These qubba-s are grave monuments of two nineteenth century Circassian governors-general of the Sudan in the service of Viceroy Muhammad ’Ali and his descendants. In the qubba-s can be seen the passing of an extraordinary age of Circassian prominence in the Nile Valley. Several events contributed to the end of the Circassian importance in international affairs in general and in Egypt in particular, including (a) the elimination of Mamluk recruitment; (b) the conquest of a divided Circassia by Russia; (c) the exile of many Circassians to Turkey, Jordan, and other points in the Middle East; (d) the growth of Arab nationalism in Egypt and other parts of the Ottoman Empire; and (e) the momentous changes in the power structure of the Ottoman government that culminated in the revolution of the Young Turks. (Ed.)